Kewajiban Pengusaha Dalam Penerapan P3K Atas Keselamatan Dan Kecelakaan Kerja Di Tinjau Dari Hukum Positif Di Indonesia Tentang Ketenagakerjaan: (Studi PT. Alfaria Trijaya Tbk) - Baiq Indi Cahya Aulya; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2023)
This research’ purposes are to know and to analyze implementation of implemented P3K by the company in their workers as the form PT. Alfaria Trijaya’s responsibilities in the work accident. This study was empirical legal research. Research’s result shows that implementation of P3K in PT. Alfaria Trijaya Tbk, can be said has been done according to the Ministry of Manpower Regulation Number 15 /MEN /VIII/2008 on the first assistance during work accident in workplace. It start with the first assistance officers, rooms, first aid cabinet or box and its contain, evacuation tools and transportation. However, the first aid implementation of company has not meets the standard according to the ministry regulation. The liability of PT Alfaria Trijaya Tbk in the event of a work accident in the workplace, as for the forms of liability including: Such as the provision of first aid for work accidents in the workplace (P3K), and the Employment Social Security Administration Agency (BPJS) covering transportation costs; Temporary compensation for being unable to work (STMB); Disability compensation; Compensation for death, funeral expenses and periodic compensation at once; Rehabilitation costs in the form of replacement of assistive devices (orthoses) and/or replacement devices (protheses); Reimbursement of dentures, hearing aids and glasses; Education Scholarship.